Investigation of thermal properties of citric acid modified magnetic nanofluids and distributions of drops deposition patterns affected by thermal strategies - Liu, Ze-Yu (2021)
Over the past decades, the increasing interests in nanofluids offer more potential to control various performances in different applications. Magnetic nanofluids (MNFs) have been extensively studied in many thermal applications due to both the magnetism and the fluidity. Both stability and thermal properties are important indicators in the process of applications. Moreover, poor colloidal stability leads to particle aggregations even precipitations, which results in clogging of flow channels and the pressure drop. Consequently, nanofluids studied in this way cannot be reliable for practical applications due to unstable physical properties. The first aim of this work is to investigate the synthesis procedure and thermal properties of well-dispersed MNFs. In terms of the synthesis, citric acid (CA) modified MNFs are prepared by a two-step method. The synthesis results show that the stability of CA modified MNFs is sensitive to pH values. The MNFs exhibit well-dispersed distribution when pH is at neutral values. Meanwhile, thermal conductivity can be predicted by the Maxwell model, and the proper aggregation can improve thermal conductivity. For convective heat transfer, it shows that the convective heat transfer of MNFs increases by 10% when the Reynolds number is over 2500. Meanwhile, a similar enhancement is obtained in the thermal efficiency of the solar collector. The experimental results show that the thermal efficiency of parabolic trough solar collector, 0.05 vol.% of MNFs, has a great potential enhancement, which is 25% higher than that of the water-based absorber and 12% higher than that of the selective surface absorber under the external magnetic field. Apart from that, due to the well-dispersed property, the deposition pattern of MNFs is also studied in the following section.